Wound healing effects and antibacterial properties of heterologous platelet-rich plasma on Staphylococcus aureus induced septic wounds in rabbits (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: This study has been designed to determine the effectiveness of heterologous platelet-rich plasma (hPRP) against infected wounds in rabbits. Materials and Methods: Staphylococcus aureus contamination was present in 24 surgical incisions, each 8 mm in diameter. The animals were then divided into two groups as follows: group A, also known as the hPRP group, received topically applied, freshly manufactured hPRP twice weekly, and group B, also known as the control group, only received sterile saline. Evaluations of the histological architecture of wounds, posttherapeutic morphology, morphometry, and in-vitro and in-vivo antimicrobial potentials of hPRP were made. Results: Rabbits that were given hPRP exhibited quicker rates of wound contraction and shorter healing times. The samples from day 7 in the hPRP group showed less inflammation and more structured fibroblasts than those from the control wounds, according to histological analysis. On day 21 of the histological examination, the hPRP group’s epidermis showed notable thickening. As demonstrated by in-vitro antibacterial activity, undiluted hPRP successfully suppressed S. aureus growth. A serum biochemical analysis showed that hPRP had no harmful effects on the liver or kidneys. Conclusions: Based on the findings of the histological features, antibacterial properties, and wound morphology, it can be said that hPRP gel holds promise as an alternative to antibiotics for the treatment of wound infections.  J. Adv. Vet. Anim. 9(3): 481–489, September 2022http://doi.org/10.5455/javar.2022.i617